FRI0362 Contrast-enhanced ultrasound of the sovraortic arteries: the potential role in monitoring disease activity and response to treatment in large vessel vasculitis. (23rd January 2014) - Germanò, G.; Macchioni, P.; Possemato, N.; Addimanda, O.; Salvarani, C.
Abstract : Background: Promising data has been recently published about the role of contrast-enhanced ultrasound (CEU) in the diagnosis and follow up of Takayasu arteritis (TA) -1, 2 - Objectives: To assess the role of CEU examination of the carotid artery in patients with large vessel vasculitis (LVV) compared to Positron Emission Tomography (PET). Methods: 10 patients (8 TA, 2 LVV, mean age 46±19y, mean disease duration 3.9±3.1y ) were contemporary evaluated with total body PET and carotid arteries US gray scale and CEU (Esaote MyLab70, 13-5MH linear probe, contrast agent Sonovue). All the patients underwent complete clinical examination and laboratory determination of acute phase reactants. Imaging results were reported using a semiquantitave score ranging from 0 (no activity) to 3 (high activity). Comparison between the two tests were made using Cohen K test. Results: At US gray scale examination 8/10 patients have high intima/media thickness (mean 1, 5 mm ±0.46). In patients with positive contrast enhanced ultrasound themean carotid intima-media thickness was 2, 1mm ±0.48, while patients withnegative contrast enhanced ultrasound presented a mean wall thickness of 0, 9mm ±0.47 (P = 0.009). There was no significant differences in clinical, demographic and laboratory data between patients with active and inactive disease. All the 4 patients with high/medium carotid activity at PET examination presented positive (activity score >1) CEU. Five of the 6 patients with low/absent PET signal have negative (activity score <2) CEU (K test = 0.800, good concordance). Conclusions: CEU have a good concordance with PET. These results outline the potential role of CEU to be used in monitoring disease activity and response to treatment in LVV. References: Magnoni M. et al.; Assessment of Takayasu arteritis activity by carotid contrast-enhanced ultrasound. Circ Cardiovasc Imaging. 2011 Mar;4(2):e1-2. Giordana P et al.; Contrast-enhanced ultrasound of carotid artery wall in Takayasu disease: first evidence of application in diagnosis and monitoring of response to treatment. Circulation. 2011;124:245-7. Disclosure of Interest : None Declared